Squeezed [compact disc, unabridged] : why our families can't afford America - Quart, Alissa (Harper Audio, 2018)
In the tradition of Barbara Ehrenreich and Jennifer Senior, this weaves together original research and reporting to investigate how the high costs of American parenthood have bankrupted the middle class, and examines solutions that might help families across the country.